Comparing the Prevalence of Gastrointestinal Disorders between Day Workers and Shift Workers at Kerman University of Medical Sciences: gastrointestinal disorders between day workers and shift workers - Rahimimoghadam, Somayeh; Khanjani, Narges; Naderi, Maryam; Rasekh, Raziyeh (Asian Pacific Journal of Environment and Cancer, 2020)
Background and Aims: Shift work can lead to adverse health effects including gastrointestinal and cardiovascular disorders. The recent study aimed to compare the prevalence of gastrointestinal disorders among day work nurses, shift work nurses and office employees of Kerman University of Medical Sciences, Kerman, Iran. Methods: This was a cross-sectional study conducted in 2011. In this study, 159 nurses working at hospitals affiliated to Kerman University of Medical Sciences and 167 office employees of the same university participated. Data was obtained using a researcher-made questionnaire and was analyzed by SPSS 18., Chi-square test and ANOVA was used for analysis. Results: Results showed anorexia (P=0.0001), dyspepsia (P=0.002), nausea (P=0.001), hiccups (P=0.003) and heath burn (P=0.002) were more prevalent among shift workers than day workers. The results also showed that the prevalence of anorexia (P=0.02), gastric ulcers (P=0.04) and heartburn (P= 0.02) was more prevalent among nurses with irregular shift work than those with regular shiftwork. Among the demographic characteristics, gender was related to the nausea (P=0.004), and nausea was more prevalent in women (4.3, 95% CI: 1.7-6.3). Also, increased age was related to heartburn (P= 0.02) Conclusion: Gastrointestinal disorders are more common in shift workers. Nurses with more ability to cope with these adverse effects should be chosen for shift work. More ways to reduce the negative health effects of shift work should be investigated.